Kant and Saussure - Muller, Robin M. (Rivista Italiana di Filosofia del Linguaggio, 2010)
This essay stages an intervention by Saussure in Kant’s account of the formation and application of empirical concepts. It takes the shape of a productive comparison of Kantian concept formation and Saussure’s “language mechanism.” My thesis is that whereas for the Kant the interplay of concept and intuition constitutes the achievement of cognition, for Saussure it is the condition of possibility of cognition, without at the same time being its completion. I conclude that Saussure’s linguistic program yields a conceptual framework given in and as language, which framework must be reapplied to sensible manifolds in order to yield experience. The essay comprises three central components: (1) I begin with a recountal of Saussurean linguistics with attention to certain motivations it shares with Kant; (2) I rehearse the fundamentals of Kantian cognition to demonstrate the sense in which signs are underpinned by the same synthesis of form and content, in light of which I clarify how signs function as formal rather than substantial entities. I also give an account of empirical concept formation as governed by the acts governing the language mechanism, arguing that we must turn attention to the social nature of language and language learning; finally (3) I show how the preceding insights hold at the level of pure concepts or categories, hence how rational grammar is also already linguistic.